A Double‐Helix Metal‐Chain Metal‐Organic Framework as a High‐Output Triboelectric Nanogenerator Material for Self‐Powered Anticorrosion. (23rd August 2022) - Shao, Zhichao; Chen, Junshuai; Gao, Kexin; Xie, Qiong; Xue, Xiaojing; Zhou, Shuangyan; Huang, Chao; Mi, Liwei; Hou, Hongwei
Abstract: The development of novel metal organic framework (MOF) friction power generation materials with high stability is important. This paper reports the first example of a double‐helix metal chain organic framework with a network structure (ZUT‐8). ZUT‐8 shows high chemical stability, functional adjustability, and excellent output performance of friction power generation, which is superior to traditional coordination polymer materials. The cathodic protection system with ZUT‐8 can prevent metal corrosion significantly. The output performance can be improved effectively by enhancing the conjugate effect of the linker. The theoretical calculation results showed that an increase in the degree of conjugation could significantly reduce the band gap, thereby affecting the friction power output signal. This study opens the door to constructing MOF materials with a double‐helix metal chain and will promote their potential applications in self‐powered electrochemical cathodic protection. Abstract : The first example of a double‐helical metal‐chain metal–organic framework (MOF) with a network structure (ZUT‐8) is prepared. It shows high chemical stability, functional adjustability and excellent output performance of friction power generation, which is superior to traditional coordination polymer materials. The highly conjugated ZUT‐8 structure was introduced into a cathodic metal‐protection system where it significantly decreases metal corrosion.